VIR potato doublet collection, its significance for breeding - S. N. Travina (Овощи России)
Relevance and research material. In 2023, it was 100 years since the beginning of the collection, study and preservation of the world doublet collection of potatoes (UNU, registration USU_505851) at the Polar Experimental Station of the VIR branch. This is one of the oldest and unique potato collections, the preservation of which is carried out in the field. The first potato samples began to enter the collection in 1923. Now the potato doublet collection has 3200 samples. It includes breeding varieties, hybrids, cultivated South American potato species Solanum andigenum Juz. et Buk, Solanum chilotanum Hawkes.Results. The collection is a unique genetic material that is of high importance in solving issues of improving the efficiency of agriculture in the country. As part of the field collection of potatoes, the source material for dangerous quarantine objects is quite widely presented: potato cancer (Synchytrium endobioticum (Schilb.) Persiva) and globoderosis (Globodera rostochiensis Woll.). There are donors of late blight resistance (Phytophthora infestans (Mont.) de Bary.). There is a source material in the collection that has economically valuable characteristics: precocity, frost resistance, yield, marketability. Varieties with a high amount of phenolic compounds in the tuber pulp are also included in the field doublet collection. Such varieties are suitable for dietary nutrition and can be used in the prevention of a number of diseases.Conclusion. The collection of the collection is of great importance for applied research and for ensuring food security of the region and the country as a whole.